Higher education key to achieving MDG - Abd Razak, Dzulkifli (2010)
SOME 30 million children reportedly do not receive basic training in reading, writing and arithmetic in Commonwealth countries. New Zealand, for example, is at one end of the scale with 80 per cent of its student population in higher education, while Sierra Leone is at the other extreme, with a mere two per cent. The role of higher education in meeting the Millennium Development Goals (MDG) is a priority, says Commonwealth SecretaryGeneral Kamalesh Sharma.